Pengaruh Perubahan Tarif, Pemahaman Peraturan Perpajakan dan Kesadaran Pajak terhadap Kepatuhan Wajib Pajak UMKM di Kabupaten Sukoharjo - Zahro Rustiana; Indra Lila Kusuma; Suhesti Ningsih (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study aims to examine the effect of changes in tax rates, understanding of tax regulations, and tax awareness on the compliance of UMKM taxpayers. This research employs a survey approach with data collection via questionnaires from respondents who are UMKM taxpayers within the jurisdiction of KPP Pratama Sukoharjo. This study uses a sample of 100 determined using the Slovin formula. The data is analyzed using multiple linear regression analysis with SPSS software. The t-test results indicate that all three independent variables have a positive and significant effect on taxpayer compliance, with the calculated t-values being greater than the t-table value (1.984) and the significance value below 0.05. This research proves that changes in tax rates, understanding of tax regulations, and tax awareness affect the compliance of UMKM taxpayers.